Effectiveness of kaolin clay particle film in managing Helopeltis collaris (Hemiptera: Miridae), a major pest of cacao in the Philippines - Amalin, Divina M. (Animo Repository, 2015)
Summary The use of particle film technology has not been documented previously to protect cacao (Theobroma cacao L.; Malvales: Malvaceae) against insect feeding. Laboratory assessment of the use of local kaolin against the cacao mirid bug, Helopeltis collaris Stal (Hemiptera: Miridae), revealed a highly positive and statistically significant repellence of this insect pest on kaolin-treated cacao pods. This result warrants follow up field studies to evaluate further the potential of kaolin clay to control cacao pests in the Philippines.